2022
DOI: 10.1002/essoar.10512378.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homeowner Flood Risk and Risk Reduction from Home Elevation between the 100- and 500-year Floodplains

Abstract: Floods inflict significant damage even outside the 100-year floodplain. Thus, restricting flood risk analysis to the 100-year floodplain (special flood hazard area (SFHA) in the U.S.A.) is misleading. Flood risk outside the SFHA is often underestimated because of minimal floodrelated insurance requirements and regulations and sparse flood depth data. This study proposes a systematic approach to predict flood risk for a single-family home using average annual loss (AAL) in the shaded X Zonethe area immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the next 30 years, flood-related property damage may increase by 60% as a result of climate change (Sastry, 2021 ), and many communities and individuals underestimate the potential for flood damage (Burningham et al, 2008 ; Mol et al, 2020 ). Therefore, many researchers worldwide have focused on flood risk and loss assessments (e.g., Dutta et al, 2003 ; Scawthorn et al, 2006 ; Tam et al, 2014 ; Afifi et al, 2019 ; Mostafiz et al, 2021a , d ; Al Assi et al, 2022a , b ; Jin et al, 2022 ; Rahim et al, 2022a , b ) and the value of mitigating the flood risk (Taghinezhad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the next 30 years, flood-related property damage may increase by 60% as a result of climate change (Sastry, 2021 ), and many communities and individuals underestimate the potential for flood damage (Burningham et al, 2008 ; Mol et al, 2020 ). Therefore, many researchers worldwide have focused on flood risk and loss assessments (e.g., Dutta et al, 2003 ; Scawthorn et al, 2006 ; Tam et al, 2014 ; Afifi et al, 2019 ; Mostafiz et al, 2021a , d ; Al Assi et al, 2022a , b ; Jin et al, 2022 ; Rahim et al, 2022a , b ) and the value of mitigating the flood risk (Taghinezhad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of this gap in scientific analysis ripple into many facets of flood awareness, communication, modeling, planning, preparation, and recovery (Huang and Xiao, 2015 ). Thus, improved quantification of flood hazards, and therefore flood risk, is crucial not only for its own sake, but also for the benefit of other, related efforts to reduce flood-induced losses to life and property (Merz et al, 2014 ; Mostafiz et al, 2021b , 2022a ; Al Assi et al, 2022a ; Gnan et al, 2022a ; Rahim et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the water depth above the first finished floor is strongly correlated with total building damage ratios. Some recent studies have applied FFH indirectly or directly along with the number of stories, basement existence, area, and unit area repair cost in USD to calculate the average annual loss in Louisiana, USA (Al Assi, Mostafiz, Friedland, Rahim, & Rohli, 2023; Al Assi, Mostafiz, Friedland, Rohli, & Rahim, 2023; Gnan et al, 2022). Another application of FFH is in flood insurance models and setting premium policies, for example, Flood Risk 2.0 is a flood insurance model introduced by FEMA.…”
Section: Introductionmentioning
confidence: 99%